Administrative Constraint’s on Teachers’ Effectiveness in Government Secondary Schools in Kebbi State, Nigeria. - Umaru, Dan Asabe; Alhaji, Kulu (NIU Journal of Humanities, 2018)
This paper focuses on the administrative constrain of teacher effectiveness of secondary schools in kebbi state, where it tries to discuss on the curriculum implementation, community relation and motivational factors which are part of the contributing factors that stem as a constrain to teacher effectiveness; with the following objectives: to examine the relationship between administrative constrain and teacher effectiveness and to measure the level of teacher effectiveness and administrative constrains.The instrument used for the collection of data is questionnaire, where by descriptive approach was used as the design for the study. The concept of teacher effectiveness was elaborated. The findings reveal that 85% of teachers are not motivated by their administrators which affect their effectiveness. Finally this paper gave recommendation that will help to improve the teacher effectiveness in secondary schools of kebbi state.